ASSESSMENT OF THE SURVIVAL AND GROWTH RATE OF SOME HARD CORAL SPECIES REHABILITATED IN LY SON MPA, QUANG NGAI PROVINCE - Ben, Hoang Xuan; Quang, Thai Minh; Hoang, Phan Kim; Dat, Mai Xuan; Tuyen, Hua Thai; Khang, Nguyen An (Vietnam Journal of Marine Science and Technology, 2019)
The total 3,630 foliose corals belonging to Pachyseris speciosa, Merulina scabriculata, Montipora verucosa and Echinopora lamellosa species were translated to restoration in Ly Son MPA. Translated hard corals to restoration were successfully and effectively rehabilitated by using techniques to attach fragment on dead coral substratum and concrete sink (reef balls). Mean survival rate of coral fragments ranged from 96.9% (± 2.7 SD) to 98.5% (± 1.3 SD) on the concrete sink and dead coral substratum, respectively. The growth rate of three species Echinopora lamellosa, Merulina scabriculata and Montipora verucosa ranged between 1.5–2.1 mm/month and did not differ between concrete sink, dead coral substratum and control (P > 0.05). Meanwhile Pachyseris speciosa showed a low growth rate of 0.9–1.5 mm/month which was significantly different between translated fragments and control (P < 0.05). The rehabilitation and protection activities of coral reefs in Ly Son should be continued and expanded, contributing to the protection of biodivesity and marine resource for sustainable economic development.